Pemanfaatan Aplikasi Pengelolah Presentase Dalam Mendukung Pembelajaran Bahasa Di SMK Swasta Satria Nusantara Binjai - Kondios Meidarlin Pasaribu; Rosnelly Siburian; Riasty Latanya Sianturi; Rindu Kaya Sinambela; Ayu Lestari Simatupang (BADAN PENERBIT STIEPARI PRESS, 2024)
The use of presentation processing applications has the potential to improve the quality of learning at Satria Nusantara Binjai Vocational School. Presentation processing applications, such as PowerPoint, Potwoon, Keynote, or Google Slides, Canva and Google sites provide various features that enable teachers and students to create interesting and interactive presentations. By using this application, teachers can visualize learning concepts more clearly through pictures, graphs and videos. Meanwhile, students can learn in a more interesting way and be involved in the learning process. This PKM activity is carried out using the demonstration method by way of presentation. This is done so that PkM activity participants listen to explanations regarding the Google Sites application and can see firsthand the practice of how to use the Google Sites application. Google sites really helps students in easily creating personal websites or blogs, creating group or team websites to share information and collaborate. Apart from helping students, Google Sites also helps teachers create educational websites to provide learning materials to students or share information with parents.